2017
DOI: 10.1016/j.bjorl.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Carotid blowout syndrome in patients treated by larynx cancer

Abstract: Carotid blowout syndrome is an uncommon complication in patients treated by larynx tumours. According to our results, patient underwent radiotherapy and patients treated with open surgical procedures with pharyngeal opening have a major risk to develop this kind of complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…They also had tumours in earlier stages than patients who were treated by radiotherapy or CRT together with resection, and were therefore more likely to survive. It has been reported that higher doses of chemotherapy and radiotherapy together with extensive resection will increase the risk of lethal complications [32]. Patients with advanced cancers of the head and neck who were admitted to hospital for more than five days during or after radiotherapy had worse locoregional control, progression-free survival, and overall survival [33].…”
Section: Discussionmentioning
confidence: 99%
“…They also had tumours in earlier stages than patients who were treated by radiotherapy or CRT together with resection, and were therefore more likely to survive. It has been reported that higher doses of chemotherapy and radiotherapy together with extensive resection will increase the risk of lethal complications [32]. Patients with advanced cancers of the head and neck who were admitted to hospital for more than five days during or after radiotherapy had worse locoregional control, progression-free survival, and overall survival [33].…”
Section: Discussionmentioning
confidence: 99%
“…Progressive fibrosis, thrombosis and obliteration of the vasa-vasorum, and weakening of the arterial walls may be observed in histologic examinations of carotid arteries, placing them at risk for rupture from nearby cartilaginous or osseous fragments. [ 2 , 21 ] This predisposes laryngeal CRN patients to CBS, which was observed in 5 (38.5%) of our cases, and 3 (60%) patients expired. In a study by McCready et al, a total radiation dose of 40 Gy in 10 days may induce damage to the vasa-vasorum and may contribute to rupture of the great arteries in dogs.…”
Section: Discussionmentioning
confidence: 70%
“…Advanced tumor staging and local recurrence along with open surgical procedures also increase the risk of CBOD-related death. 37 38 39 40 …”
Section: Discussionmentioning
confidence: 99%